Analysis of Ethnopharmacological Studies on the Use of the Sambiloto Plant in the Treatment of Malaria in the Asmat Tribal Community in Papua, Indonesia - Awotauw, Esther Lea; Ruth Maria Panggabean (Eureka Herba Indonesia, 2024)
Malaria is still a major health problem in Indonesia, especially in the Papua region. The Asmat tribe has traditional knowledge about the use of medicinal plants to treat malaria, one of which is sambiloto. This research uses a qualitative observational research design with an ethnopharmacological approach. This approach combines aspects of ethnography and pharmacology to study traditional knowledge and the use of medicinal plants in a community. It was discovered that sambiloto has long been used by the Asmat tribe to treat malaria. Sambiloto leaf is processed into a decoction or juice and drunk to relieve malaria symptoms such as fever, chills, and headaches. This ethnopharmacological study shows that sambiloto has potential as an herbal medicine for treating malaria in the Asmat community. Further research is needed to test the effectiveness and safety of sambiloto in the treatment of malaria.